OBJECTIVIZATION OF THE EFFECT OF A COMPLEX OF PHYSICAL FACTORS IN PATIENTS WITH CARPAL TUNNEL SYNDROME BY ELECTROMYOGRAM TEST (World Science, 2021)
CTS is the most common compression neuropathy with an incidence of 125-515/100 000. It is a result of compression of the median nerve by the transverse carpal ligament. It is observed in 2 to 5% of the general population, more frequently in women.Electromyography is considered the most accurate diagnostic procedure, although it cannot be fully accepted as a gold standard due to the possibility of false positives (about 15%) and false negatives (about 18%) [1]However, because of its low cost, in comparison to other diagnostic methods, its high diagnostic reliability, and the few contraindications to its application, it remains a method of choice for diagnosis and follow-up of the reinnervation of the median nerve in CTS patients.Aim of study. To investigate the effect of a complex of physical factors on the reverse development of symptoms of moderate carpal tunnel syndrome using electromyography.Materials and methods. 57 patients with mild to moderate degree of carpal tunnel syndrome clinically proven by electroneurographic study were еexamined. 38.60% of the patients were with right hand affected, 9 patients (15.80%) with left hand affected and 26 patients (45.60%) with bilateral involvement (n=26). In the last group, we examined both hands, ie 57 patients and 82 hands were investigated.Based on the analysis of our own studies, we applied the following complex physiotherapeutic program to the patients involved in the study: ultrasound, electrophoresis with Nivalin (Galantamine), and traditional kinesitherapy program.In our study, we examined the sensory and motor fibres of the n. medianus. Changes in distal latency, amplitude, and conduction velocity were observed.Results and discussion. The electroneurographic examination we performed showed a statistically significant change (p